ELAVL1 promotes prostate cancer progression by interacting with other m6A regulators - Cai, Zhonglin; Xu, Huan; Bai, Gang; Hu, Hanjing; Wang, Di; Li, Hongjun; Wang, Zhong (Frontiers in Oncology, 2022)
N6-methyladenosine (m6A) imbalance is an important factor in the occurrence and development of PCa. Many m6A regulators have been found to be significantly dysregulated in PCa. ELAVL1 is an m6A binding protein that is can promote the occurrence and development of tumors in an m6A-dependent manner. In this study, we found that most m6A regulators were significantly dysregulated in PCa, and some m6A regulators were associated with the progression-free interval. Mutations and copy number variations of these m6A regulators can alter their expression. However, ELAVL1 mutations were not found in PCa. Nevertheless, ELAVL1 upregulation was closely related to PCa proliferation. High ELAVL1 expression was also related to RNA metabolism. Further experiments showed that ELAVL1 interacted with other m6A regulators and that several m6A regulatory mRNAs have m6A sites that can be recognized by ELAVL1. Additionally, protein–protein interactions occur between ELAVL1 and other m6A regulators. Finally, we found that the dysregulation of ELAVL1 expression occurred in almost all tumors, and interactions between ELAVL1 and other m6A regulators also existed in almost all tumors. In summary, ELAVL1 is an important molecule in the development of PCa, and its interactions with other m6A regulators may play important roles in PCa progression.